Effect of cooked molasses tubs on performance and health of newly received stocker calves - Paisley, S.I.; Stokka, Gerald L.; Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eight paired comparisons conducted at three field sites with 1059 newly-received lightweight stocker calves were used to determine the effect of free-choice cooked molasses tubs designed for receiving cattle on 28-day receiving period performance, percentage of cattle treated for respiratory disease, and death loss. At all sites, cattle received similar management with the exception that cooked molasses tubs were added to half of the pens immediately following initial processing. Weight gains were similar (P=0.36) for cattle with or without access to tubs (43 and 38 lb, respectively). The addition of tubs also did not affect the number of cattle treated (P=0.48) or percent death loss (P=0.61); however, there was a numerical decrease in death loss for cattle with access to tubs (2.7 vs 1.8%). Tub consumption (0.245 lb/day) based on beginning and ending weights of the tubs, was below the desired level of 0.5 lb/day. Low tub consumption may have compromised any potential for improved performance or overall health response for cattle offered free access to cooked molasses tubs.
Keywords: Beef; Receiving; Cattle; Cooked molasses tubs